Etika bisnis dalam perspektif islam - hidayat, nur afif (Maliki Interdisciplinary Journal, 2026)
Business ethics in the Islamic perspective has become a central issue amid global economic dynamics often characterized by unethical practices such as usury, monopoly, exploitation, and market manipulation. This conceptual article analyzes Islamic business ethics through conceptual and comparative analysis of core sharia principles, including justice (al-‘adl), honesty (ṣidq), trustworthiness (amānah), the prohibition of gharar, and the prohibition of riba. The study explores how Islamic ethical principles can function as a normative paradigm in modern business practices. The findings indicate that Islamic business ethics emphasizes a balance between profit and public welfare, thereby fostering fair, sustainable, and value-oriented business practices.